Was There a Cult of El in Ancient Canaan? Essays on Ugaritic Religion and Language - Tsumura, David Toshio (Mohr Siebeck, 2024)
In this collection of essays, David Toshio Tsumura examines a number of Ugaritic mythological and liturgical texts in detail for how they interpret deity. He sheds light on ancient Canaanite religious practices and social customs essential for a better understanding of Old Testament literature.
PublicationDate: 20240304
Keywords: Israel -- Old Testament -- Ancient Near East -- Altes Testament -- Altorientalistik -- Antike Religionsgeschichte